Luminescence spectroscopy of semiconductors - Pelant, Ivan, 1944-; Valenta, Jan, 1965- (Oxford : Oxford University Press, 2012)
Semiconductor luminescence has been a rapidly expanding field over the last 50 years. This text reviews the whole subject of semiconductor luminescence in one volume.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Luminescence spectroscopy; Semiconductors -- Optical properties